What do we know about Eye and Facial Protectors : Review for COVID-19 Pandemic and Possible Future Epidemics - Jalilvand, Hadi; Meshkini, Mohammad; Meshkini, Fatemeh; Valikhanlou, Nayyereh (International Journal of Coronaviruses, 2021)
Personal Protective Equipment (PPE) is mandatory for everybody in a threatening state, they are meant to provide safety and prevent injuries especially in hazardous issues. Facial guards are mostly used for providing eyes and face from splash-kind of hazards. During the COVID-19 pandemic, their use also was recommended to longer the use of masks or respirators, due to their shortage and the excessive demand of their reuse. This review gathered the information on eye and face protectors from various manufacturer, international and local guidelines; also authors’ experiment during the COVID-19 pandemic in Iran.
Keywords: Face-Shield; Safety Glasses; Goggles; Personal Protective Equipment; Sight protection; Health-Care Provider